2022
DOI: 10.1097/nne.0000000000001243
|View full text |Cite
|
Sign up to set email alerts
|

Academic-Practice Collaboration Using Virtual Telesimulation to Support Students' Clinical Practice

Abstract: Background: Collaboration between academic institutions and clinical practice plays an important role in supporting students' learning in clinical practice. A virtual telesimulation was incorporated to provide academic-practice collaboration between academic educators and nurse preceptors to support students' clinical education. Purpose: The purpose was to evaluate the experiences of nursing students and academic educators on the perceived impact of virtual telesimulation in clinical education. Methods: A desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…For instance, students may be grouped by hospitals and receive contextually relevant information specific to their upcoming clinical practicums. This is a plausible idea as earlier research has shown that the use of such clinical simulations can improve students’ satisfaction and readiness for clinical practice [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, students may be grouped by hospitals and receive contextually relevant information specific to their upcoming clinical practicums. This is a plausible idea as earlier research has shown that the use of such clinical simulations can improve students’ satisfaction and readiness for clinical practice [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%